THE MASTERS AND JOHNSON TREATMENT PROGRAM FOR SEX OFFENDERS: Intimacy, Empathy and Trauma Resolution. - Schwartz, Mark F. (Sexual Addiction & Compulsivity, 1994)
Most contemporary treatment programs rely heavily on the cognitive-behavioral approaches to sexual compulsivity. Behaviorist ideology rests upon the premise that paraphilias such as voyeurism or exhibitionism "are built upon the foundations of learning, conditioning and the reinforcing nature of orgasm" (Tollison & Adams, 1979). For this reason, many cognitive behaviorists have, until very recently, focused treatment almost exclusively on corrective conditioning to increase nondeviant and decrease deviant sexual arousal, as well as utilizing skills approaches to improve social interaction, anger management and assertiveness, empathy, relapse prevention, and sexual information skills. Also included are techniques to alter cognitive beliefs that result in minimization or denial and rigidity. Such approaches have demonstrable effectiveness with a high percentage of individuals (Maletzky, 1991) and are critical in rehabilitation of the sex offender. However, the purpose of this paper is to argue that therapeutic programs, in order to achieve maximum effectiveness, need to move beyond such mechanistic reductionism.